Automatic Watering System on Microcontroller-Based Tomato Plants With The Fuzzy Logic Approach - Muhammad Arif Bagus Dewanto; Muhammad Rizky Alfazry; Wanda Haniyah; Fikri Fadilah; Muhammad Fakhri Firdaus; Akhtarsyah Pambudi Putra; Dwi Yulinar Chairunisa; Agung Prayudha Hidayat (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
One of the main challenges in crop cultivation is addressing irrigation issues, which are often carried out conventionally. This research aims to tackle this problem by implementing fuzzy logic in the development of an automatic irrigation system for tomato plants based on a microcontroller. The system is designed to create an intelligent irrigation solution capable of adjusting water supply according to environmental conditions and the needs of tomato plants. The research methodology includes system design, environmental data collection, and implementation of fuzzy logic algorithms for decision-making. The research findings demonstrate the effectiveness of the fuzzy logic-based approach in optimizing irrigation schedules, resulting in improved plant health and water conservation. Thus, the conclusion emphasizes the potential of fuzzy logic in enhancing precision farming practices and underscores the importance of adaptive irrigation systems in supporting sustainable crop production.